Volume 5A: Industrial and Cogeneration; Manufacturing Materials and Metallurgy; Marine; Microturbines, Turbochargers, and Small 2013
DOI: 10.1115/gt2013-94510
|View full text |Cite
|
Sign up to set email alerts
|

Study of Wash Fluid Cleaning Effectiveness on Industrial Gas Turbine Compressor Foulants

Abstract: Online compressor washing is an advanced method of mitigating the effects of fouling as well as to increase the interval between offline washes. The major concern with online compressor washing has been its cleaning effectiveness, since it is carried out when the engine is running at full or near full speed. Hence, injecting wash fluid into the compressor to achieve an efficient cleaning is a challenge. This work investigates the most appropriate wash fluid for cleaning a particular type of foulant. Contaminan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(2013) took a closer look at the cleaning effectiveness of onwing washing to remove contamination to better understand the direct impact of EW on the engine (Roupa, Pilidis, Allison, & Lambart, 2013). Igie (2017) provides a comprehensive overview of the compressor fouling effect and compressor wash for both stationary and jet engines (Igie, 2017).…”
Section: Current Research On Engine Washmentioning
confidence: 99%
“…(2013) took a closer look at the cleaning effectiveness of onwing washing to remove contamination to better understand the direct impact of EW on the engine (Roupa, Pilidis, Allison, & Lambart, 2013). Igie (2017) provides a comprehensive overview of the compressor fouling effect and compressor wash for both stationary and jet engines (Igie, 2017).…”
Section: Current Research On Engine Washmentioning
confidence: 99%
“…[64], while Mund and Pilidis [65] reported a 308 review of gas turbine online washing systems. Roupa et al [66] 309 and Brun et al [67] reported a study regarding the effectiveness of 310 cleaning fluids. Oosting et al [68] proposed some improvements 311 to on-line washing techniques in order to diminish the blade 312 erosion.…”
mentioning
confidence: 99%